Emergence phenology and temperature effect on the post-diapause egg development in the bush cricket Barbitistes vicetinus (Orthoptera, Tettigoniidae). Issue 1 (24th July 2019) - Cavaletto, G.; Faccoli, M.; Marini, L.; Mazzon, L.
Abstract: The tettigoniid Barbitistes vicetinus Galvagni & Fontana was described in 1993 as an endemic and rare bush-cricket of north-east Italy. Since 2008, this species has become a pest, causing repeated outbreaks with severe defoliations in broadleaf forests and neighbouring crops. Few data are currently available on ecology and life-cycle of this species, in particular about how temperature regulates egg-diapause and hatching phenology. The present work reports a field study regarding hatching phenology of B. vicetinus, surveyed with 84 emergence traps over four consecutive years (2013–2016). Moreover, the effect of temperature on the hatching was tested in the laboratory, exposing eggs to different temperatures. Field observations showed that hatching occurred between the end of March and beginning of April. In warmer years, hatching started early in the spring and lasted longer, while in colder years, hatching started later and was concentrated in a few days. Moreover, a significant effect of both elevation and exposure on the hatching start was observed. Results obtained from laboratory suggested the ability of the species to develop in the post-final diapause in a wide range of thermal conditions. After the diapause (terminated by a prolonged common exposure to low temperature) B. vicetinus was able to hatch from 6 to 23°C although, due to prolonged post-diapause development, hatching took place progressively later at colder temperatures. To manage B. vicetinus outbreaks, forecasting the seasonal phenology of egg hatching and its duration is important for an effective pest control.